2018
DOI: 10.3174/ajnr.a5516
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging of Brain Metastasis from Lung Cancer: Correlation of MRI Parameters with the Histologic Type and Gene Mutation Status

Abstract: Our results suggest that DWI parameters (minimum ADC and normalized ADC ratio) for the solid components of brain metastasis from lung cancer are not correlated with their histology, whereas they can predict the mutation status in brain metastasis from lung adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…The previous studies have shown certain MR imaging characteristics were associated with gene mutation status of the primary tumor [14] and were predictor for OS [15] . However, these studies did not further focus on the association between brain MRI characteristics and prognosis, and had minimal impact on the treatment decision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous studies have shown certain MR imaging characteristics were associated with gene mutation status of the primary tumor [14] and were predictor for OS [15] . However, these studies did not further focus on the association between brain MRI characteristics and prognosis, and had minimal impact on the treatment decision.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few publications focusing on ADC value as brain MR parameters and its association with BM. DWI parameters, minimum ADC and normalized ADC ratio, for the solid BM was reported to predict the EGFR mutation status in BM from lung adenocarcinoma, [14] and minimum ADC and ADC transition coefficient (ATC, ADC changes at the brain-metastasis interface) as predictor for OS [15] . We found that the high prevalence of intratumoral hemorrhage or necrosis in BM is a major technical issue, and small BM was only detected on 3D T1 imaging and too small to be measured on ADC map.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have mainly focused on the relationship between the tumor metabolism evaluated by positron emission tomography/ computed tomography with 18F‐fluorodeoxyglucose (18F‐FDG PET/CT) and genetic mutations in CRC or rectal cancer; however, with conflicting results . Magnetic resonance imaging (MRI) based on morphologic features and quantitative parameters derived by using diffusion‐weighted imaging (DWI) may help predict mutation status of various tumors . However, conventional DWI using a monoexponential model has the limitation of only assessing the Gaussian water diffusion behavior.…”
mentioning
confidence: 99%
“…[12][13][14][15][16] Magnetic resonance imaging (MRI) based on morphologic features and quantitative parameters derived by using diffusion-weighted imaging (DWI) may help predict mutation status of various tumors. [17][18][19][20] However, conventional DWI using a monoexponential model has the limitation of only assessing the Gaussian water diffusion behavior. Diffusion kurtosis imaging (DKI), an advanced non-Gaussian DWI model, can provide more precise information in terms of the heterogeneity and irregularity of tissue components.…”
mentioning
confidence: 99%